Prevalence of Left Ventricular Diastolic Dysfunction in Type 2 Diabetes Mellitus & its Association with HbA1c - LAVINA PATTNAIK; BIJOY K DASH; BEHERA, SARITA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Diabetes mellitus progressively augmented over the previous years in India and through the world, with India subsidizing a foremost part of the global encumbrance. The current study has been aimed to assess left ventricular diastolic dysfunction in diabetic person and to evaluate the correlation of diastolic dysfunction also its HbA1c range. Material and methods: This prospective, cross-sectional, observational study has been performed for one year from September 2018 to August 2019 in the Bhima bhoi medical college & Hospital, Balangir, Odisha. 70 patients of Type 2 DM have been enrolled in the present study. The primary objective of the present study is to evaluate the incidence of LVDD in cases with Type 2 DM without any prior cardiac complications. Glycosylated haemoglobin has been estimated by ion exchange resin method. 2D Doppler Echocardiography was used to diagnose LVDD. Results: A large proportion or 48.6% of the diabetics in the study were diagnosed with LVDD of grade I severity. Data revealed that increased levels of glycated haemoglobin caused the severity of LVDD to worsen. With HbA1c levels between 0-8.9 per cent, 67.4% had grade I LVDD, with HbA1c levels between 9-10.9%, majority or 76.9% had grade II dysfunction and similarly with HbA1c between 11-18%, 90.9% of patients had grade III LVDD. This correlation found to be statistically significant (p<0.00001). Conclusion: Higher values of FPG, PPPG and HbA1c were associated with higher incidence of LVDD. Thus, optimal glycaemic control may lower the risk of having early diastolic dysfunction and its progression. This has been perceived with cases with Type 2 diabetes mellitus may remain asymptomatic despite having significant left ventricular diastolic dysfunction